Symbolic and Didactic Appraisal of Lenrie Peters “The Panic of Growing Older" - Imeta Akakpo; Robert Atsu Okor; Isaac Horsu (English Education and Applied Linguistics Journal (EEAL Journal), 2025)
This paper conveys a legitimate role of poetry to society. The introductory background conveys the role of poetry in society. The students' languages learning process for improvement of understanding and decoding of the symbiotic relationships of diction and literary art are made bare. It further portrays the importance and significance of poetry to students and society. The set objectives manifest a better scrutiny of poetry in unavailing the inner perimeters of poetry analysis; the use of appropriate diction, symbols and the moral lessons attached to poems and other literary art. Based on Barthes symbiotic theory, the paper digresses the connotative and denotative use of language in Lenrie Peters' poem 'The Panic of Growing Older'. Though the theory's major focus is on symbolism and didactive meaning of work of art, how best such diction and symbols can be helpful in the interpretation of a poem are brought to bear in the analysis and discussions in this paper. The analysis of the poem translates the serious stages of man's life on earth. The discussion does not only interpret what is indicated by the poet but relay them to the knowledge of the irreversible ageing features to set a tone for awareness and expected domain one finds himself or herself at that stage of life as described by the Lenrie Petters. Certainly, the paper gears towards the lessons shared in the poem to direct the upcoming youth on expectant challenges to be prepared for as on keeps growing which is inevitable. The brilliant use of diction to denote the intention of the poet is also discussed.